Opinions of Fifth Grade Science Teachers about the 2017 Science Curriculum - Pınar Ural Keleş (Anı Publishing, 2018)
This study was conducted to understand the opinions of fifth grade science teachers about the 2017 science curriculum. The study was carried out in the fall semester of 2017-2018 academic year with 11 teachers who taught the fifth-grade science course in Ağrı province. The study was designed as a case study. Participants of the study were determined using snowball sampling method which is one of the purposeful sampling methods. The data of the study was collected by a semi-structured interview form. In the interviews, teachers were asked 8 questions. The data obtained from interviews were subjected to descriptive analysis. As a result of the study, it was determined that the teachers who participated in the research had both positive and negative opinions about the science curriculum of the 2017 science course. It is among the recommendations of the teachers to give effective and sufficient in-service training about the 2017 science curriculum.